I'm afraid too - Hambleton, Laura (London : Milet, 2001)
The little wooden man lives hapily in the pine tree in the forest. Whan his tree is chopped down the discovers his fear about the world outside his home.
Keywords: Forest -- Fiction; Trees -- Fiction; Woods -- Fiction